Global Research Trends of Six Sigma in Management: A Bibliometric Perspective - Rusyani, Erni (West Science Business and Management, 2025)
This study presents a bibliometric analysis of global research trends on Six Sigma within the management discipline, covering 747 publications indexed between 2015 and 2025 with an annual growth rate of 2.3 percent. The findings reveal a fluctuating yet generally positive publication trajectory, with notable peaks in 2020 and 2023, likely driven by global operational challenges and subsequent organizational restructuring. Geographic distribution indicates a strong concentration of research in a few countries, led by India, the United States, and the United Kingdom, reflecting disparities in research capacity and collaboration networks. Keyword co-occurrence mapping identified key thematic areas, including methodological foundations such as DMAIC and process improvement, strategic themes like critical success factors, sustainability, and Industry 4.0 integration, as well as sector-specific applications in healthcare, public services, and SMEs. The results underscore the multidisciplinary nature of Six Sigma and its evolution from a technical quality improvement tool to a strategic management framework, increasingly integrated with complementary approaches such as Lean, the Theory of Constraints, and ITIL. This adaptability enhances its relevance in diverse industrial contexts, contributing to operational excellence, strategic advantage, and customer satisfaction. Future research should explore digital technology integration, cultural and institutional adoption factors, and the long-term strategic impacts of Six Sigma to strengthen its global applicability.